GAMBARAN PROSES MANAJEMEN LOGISTIK FARMASI DI GUDANG FARMASI RS PKU MUHAMMADIYAH KOTA YOGYAKARTA - Syarifah Auliatul Rizka Maulida (International Journal of Healthcare Research, 2019)
Logistics management in hospitals is one of the important aspects in hospitals. Availability of medicines is currently a demand for health services. Drug logistics management in hospitals includes the stages, namely planning, procurement, storage, distribution, deletion, evaluation and monitoring which are interrelated with each other, so they must be well coordinated so that each can function optimally. Purpose: To knowing the description of the pharmaceutical logistics management process in the pharmaceutical warehouse of PKU Muhammadiyah Hospital Yogyakarta. Methods: This research is qualitative research with observation and interview method for data collection in Pharmacy Logistics at PKU Muhammadiyah Hospital Yogyakarta.Results: The logistics management process in the pharmacy section of PKU Muhammadiyah Hospital is implemented by selecting pharmaceutical preparations, planning, procurement, receiving, storing, distributing, destroying and withdrawing, and controlling. Conclusion: Pharmaceutical logistics management at PKU Muhammadiyah Hospital is carried out by competent officers and in accordance with the hospital's internal regulations.